(untitled) (KULT_online, 2021)
Traveling through the spaces of political actions and performing arts of the 2010s, mostly in Western European countries, A Live Gathering: Performance and Politics in Contemporary Europe looks into a new phase of relationships between these two fields. Asking about the potential of performance to embody the experience of politicality, the book provokes the discussion about alternative modes of participation in politics when artists’ and audiences’ imagination becomes a vehicle to overcome political predicament on the road to democracy.